Dioxepin-maleik anhidrit kopolimerlerinin sentezi - Odabaş, Şeniz (Fen Bilimleri Enstitüsü, 1995)
Halen üzerinde çeşitli çalışmalar yapılan 4,7-dihid- ro-1,3-dioxepinler maleik anhidrit ile kalayca polimerle- şerek düşük molekül ağırlıklı polimerler elde edilir. Bu çalışmada yeni sentezlenmiş orijinal 4,7-dihidro- 1, 3-dioxepin türevlerinin maleik anhidritle serbest radikal polimerizasyonu yapılmıştır. Çalışmada öncelikle dioxepinler yeniden sentezlenip, kristallendirme veya va kum destilasyonu metotlarıyla polimerizasyon öncesi saflaştırılmıştır. Polimerleşme reaksiyonları azot atmosfe ri altında 70-80aC sıcaklıkta AIBN başlatıcısı ile orta lama 7-8 saatlik sürelerde çözücülü ve çözücüsüz ortamlarda gerçekleştirilmiştir. Çözücü kullanıldığında özellikle yapısında su tutmayanlar ve maleik anhidritle reaksiyon vermeyenler seçilmiştir. Yeni sentezlenen orijinal kopolimerlerin saklanması güç olduğundan, maleik anhidritteki hidroliz alabilecek anhidrit yapısı, metanal ile ester haline getirilmiştir. Modifikasyon asitsiz ortamda yaklaşık 12 saatlik sürede metanal fazlası ile geri soğutucu altında kaynatılarak yapılmıştır. Kopolimerlerin asidik ortamda hidrolizlerime düşünülmüş, fakat dioxepin halkasının bu şartlarda açılarak dial haline gelmesi ve kopolimerlerden hep aynı ürün oluşacağından bu uygulamadan vazgeçilmiştir. Sentezlenen kopalimerler susuz polar çözücülerle sey reltilip, apolar çözücülerde çöktürülmüştür ve vakum etüvünde kurutulmuştur. i Polimerlerin yapısı I.R ve H-NMR ile aydınlatılmış. Sonuç olarak Cannon-Fanske viskozimetresi ile viskoziteleri ölçülmüş, ortalama molekül ağırlıkları tayin edilmiş tir.

Diaxepins capalymerize with certain electron accepting monomers to farm a copolymer containing approximately 50 mole percent dioxepin. This electron accepting monomer comprises maleic anhydride which does not homopolymerize, and also dioxepin does not, in the polymerization. Dioxepin is dermatologically safe. Therefore a copolymer formed from dioxepin, mould provide a dermato logically safe polymer. In this study k, 7-Dihydro-1, 3-dioxepin derivatives and maleic anhydride were copoymerized by using AIBN as free radical initiator at 70-80aC. Diaxepins are resynthesized and also purified by recrystallization or vacum destination before used.. The resulting prgducts were characterized by FTIR and H NMR. In the following table the reaction products of cis 2-buten-1,k dial with carbanyl compound were summarized. The formation of copolymers is accomplished by free radical polymerization. 2, 2-Azobisisobutyronitrile (AIBN) was used as an initiator. If dioxepin is liquid the polymerization may be effected in bulk. Where a bulk process is used, the polymerization is normally carried out at a temperature at which an initiator will perform and the temperature should not be so high that the dioxepin decomposes. It is preferred to effect polymerization at temperatures from 7D°C to BQ°C. If dioxepin is solid the polymerization may be effected in solution, the solvents should be substantially anhydrous, Toluen is used as a solvent in the polymeriza tion reactions. TABLE: 1. Ths Reaction Products of Cis-2-Buten 1,4-Dial With Carbonyl Compounds. Carbanyl Compound Product 0 / v 0- W,V-H ö V ©>o: 0C2H5 Br- CH2- CH X3C2H5 CH"QH n I 2 //° CH,- C- C 3 I \ cm H Br- CH2-{ CH20H Q- CH3-C ( CH. VI The time of the reaction was varied depending on the reagents, initiator and solvents, but generally varied between k to 1 2 hours. Stoichiametrically, the reaction was conducted with one to one molar proportion of 1, 3-dioxepin to maleic anhydride. To insure a 1 :1 polymer, it is preferably to have a slight molar excess of dioxepin. The dioxepin is also easier to separate. The polymerization was preferably conducted in an inert, dry atmosphere to avoid contamination or oxidation of the reagent nitrogen was used as an inert atmosphere in this work. According to the preceeding method, copolymers containing a 4,7-dihydro 1, 3-dioxepin and maleic anhydride represented by the following formula. ^X /C^ Polymerization conditions Reaction temperature Reaction time Initiator Solvent Suitable atmosphere 75-80uC 6-12 hrs AIBN Toluen Nitrogen The structure of polymers is summarized in the Table 2, and Table 2. a. Vll TABLE: 2. Proposed Structure of Prepared 1,3-Dioxepin Maleic Anhydride Copolymers 1,3-Dioxspin Copolymer CH- "CH 3 ~CFW.ooD D o CH, n (A) G ^0 o'^o' **0 (B) y ^0 o o ^^QX-S 0 C C n "(C) vm TABLE: 2. a. Proposed Structure of Prepared 1,3-Dioxepin Maleic Anhydride Copolymers 1, 3-DİDxepin Copolymer 1 - T / --o" _ n (D) CH20H I 0 a ch3 -c -{ CH. CH,-C-CH"DH 3, 2 CH" C =0 C=D I ! ?H OH n (F) IX Coplymers of 4,7-Dihydro-1, 3-diaxepin uith maleic anhydride are not hydrolytically stable under atmospheric conditions. Conversion of copolymer to relatively stable form was accomplished by the following reaction. CH30H Copolymer > The composition of copolymer and modified copolymer was estimated from I.R and H-N.M.R spectra. All the copolymers revealed similar characteristic absorbecies. Anhydride carbonyl group at 1B60, 17B0 cm", anhydride C-D at 172G cm"T and 1180 cm". Viscosity af the polymers was determined at 30 C using 50 mg/1 0 ml of dimethyformamide solution in a Cannon-Fenske viscometer. The inherent viscoisty of the polymers was very low. Hence the number average molecular weights are from 10000-4-0000.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1995
Keywords: Dioxepin; Kopolimerler; Maleik anhidrit; Sentez; Dioxepine; Copolymers; Maleic anhydride; Synthesis